The Prognostic Value of Adjuvant Chemotherapy in Colon Cancer With Solitary Tumor Deposit - Lin, Qiangkang; Zhou, Huizhen; Shi, Si; Lin, Jixu; Yan, Wangxin (Frontiers in Oncology, 2022)
Purpose The aim of this study is to investigate the survival benefit of adjuvant chemotherapy in patients with colon cancer with the solitary tumor deposit (TD). Methods The primary study outcomes used in this study were colon cancer–specific survival (CSS) and overall survival (OS). The differences of the distribution of categorical variables in patients with colon cancer with the solitary TD according to adjuvant chemotherapy administration were tested using the Pearson’s chi-square test. The Kaplan–Meier method was utilized to evaluate CSS and OS. Hazard ratio (HR) and 95% confidence interval (CI) were calculated on the basis of Cox regression models to assess the prognostic value of different demographic and clinicopathological characteristics. Results A total of 877 patients with TanyN1cM0 colon cancer with solitary TD were identified in our analysis. It was found that OS (75.4% vs. 42.8% for 5-year OS rate, p < 0.001) and CSS (82.9% vs. 69.3% for 5-year CSS rate, p < 0.001) of patients with colon cancer with adjuvant chemotherapy administration were significantly better than those without adjuvant chemotherapy administration. Multivariate Cox survival analyses revealed that the overall and colon cancer–specific mortality risks of patients with adjuvant chemotherapy administration were decreased by 64.4% (HR = 0.356, 95% CI = 0.265–0.479, p < 0.001) and 57.4% (HR = 0.426, 95% CI = 0.286–0.634, p < 0.001) compared with those without adjuvant chemotherapy administration, respectively. Conclusions Adjuvant chemotherapy administration could significantly improve OS and CSS in patients with colon cancer with the solitary TD. This is the first study to investigate and demonstrate the survival benefit of adjuvant chemotherapy in patients with colon cancer with the solitary TD.